CURRENT SOCIO-ECONOMIC RISK FACTORS WITHIN CHILD TRAFFICKING IN SOMALIA - Arianto, Nabila Triwulandari; Sofie, Jasmine Nabila; Mallu, Zsa Zsa Nurfajriah; Surayya, Dina Pasya; Prakoso, Septyanto Galan (Jurusan Ilmu Hubungan Internasional, 2024)
Children are one of the victims of human trafficking in Somalia. In 2020 alone, there were approximately 3.100 victims of child trafficking in Somalia. Most incidents involve are child abductions for various reasons, including armed groups and even sex workers. The Covid-19 pandemic somehow made the condition worse, when the problem of trafficking amplified by the socio-economic factors. The purpose of this research is to answer the question of how socioeconomic factors contribute to Somalia's high rate of child trafficking, especially during the Covid-19 pandemic. This research will employ a descriptive qualitative method, and rely on secondary data sources in the form of literature studies employing journal articles, news, official government documents and archives, and other supplementary data. Human security concept and human needs theory will be utilized to support the analysis on this study. In addition, this research seeks to serve as a resource for readers and academicians who study child trafficking cases, especially in Somalia. This study found that the prevalence of child trafficking in Somalia influenced by-the country's socio-economic climate, specifically during Covid-19 pandemic.